Political Communication Through New Media In Local Elections In Indonesia - Refly Setiawan; Munadhil Abdul Muqsith; Elmira Avzalova; Mohamad Fikri Sulthan; Stanislav Vladimirov Mladenov (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
AbstractNew media is one of the supporting facilities for the development of democracy in Indonesia. In the current era of globalization, people are required to be able to adjust to advances in technology and information to support the delivery of people's aspirations through new media. The new media is the right step to carry out political communication in the midst of society, even more so at this time it is not possible for politicians to be able to communicate and campaign directly to the public given the implementation of the New Normal and the continued spread of the Covid-19 pandemic in Indonesia. This study aims to determine political communication through new media related to the elections in Indonesia and how the role of new media related to political communication activities carried out at this time. The research method used in this research is descriptive qualitative research method. The results showed that the presence of new media in Indonesia drastically changed the course of politics and democracy in Indonesia. In addition, political communication through new media such as the internet and social media in the elections in Indonesia is considered as one of the effective and efficient breakthroughs considering the current conditions in the Republic of Indonesia are unstable due to the Covid-19 pandemic and obliging all people to remain compliant with government regulations.Keywords: Political Communication, New Media, Local Elections in Indonesia AbstrakMedia baru merupakan salah satu sarana penunjang pengembangan demokrasi di Indonesia. Di era globalisasi saat ini masyarakat dituntut untuk dapat menyesuaikan diri dengan kemajuan dibidang teknologi dan informasi guna mendukung penyampaian aspirasi masyarakat melalui media baru. Media baru merupakan langkah tepat untuk melakukan komunikasi politik ditengah masyarakat terlebih lagi saat ini sangat tidak memungkinkan bagi para politisi untuk dapat berkomunikasi dan berkampanye secara langsung kepada masyarakat mengingat penerapan New Normal dan masih adanya penyebaran pandemic Covid-19 di Indonesia. Penelitian ini bertujuan untuk mengetahui komunikasi politik melalui media baru terkait pilkada di Indonesia dan bagaimana peran media baru terkait aktivitas-aktivitas komunikasi politik yang dijalankan saat ini. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian deskriptif kualitatif. Hasil penelitian menunjukkan bahwa Kehadiran media baru di Indonesia mengubah secara drastis perjalanan politik dan demokrasi di Indonesia. Selain itu, Komunikasi politik melalui media baru seperti internet maupun media sosial dalam pilkada di Indonesia di nilai sebagai salah satu terobosan yang efektif dan efisien mengingat saat ini kondisi di Republik Indonesia sedang tidak stabil karena pandemic Covid-19 dan mewajibkan seluruh masyarakat untuk tetap patuh terhadap peraturan pemerintah.Kata Kunci: Komunikasi Politik, Media Baru, Pilkada Di Indonesia